SARS-CoV-2 Modulation of HIV Latency Reversal in a Myeloid Cell Line: Direct and Bystander Effects - Jarmoluk, Patricio Gabriel (2024)
Coronavirus disease 2019 (COVID-19) might impact disease progression in people living with HIV (PLWH), including those on effective combination antiretroviral therapy (cART). These individuals often experience chronic conditions characterized by proviral latency or low-level viral replication in CD4+ memory T cells and tissue macrophages. Pro-inflammatory cytokines, such as TNF-α, IL-1β, IL-6, and IFN-γ, can reactivate provirus expression in both primary cells and cell lines. These cytokines are often elevated in individuals infected with SARS-CoV-2, the virus causing COVID-19. However, it is still unknown whether SARS-CoV-2 can modulate HIV reactivation in infected cells. Here, we report that exposure of the chronically HIV-1-infected myeloid cell line U1 to two different SARS-CoV-2 viral isolates (ancestral and BA.5) reversed its latent state after 24 h. We also observed that SARS-CoV-2 exposure of human primary monocyte-derived macrophages (MDM) initially drove their polarization towards an M1 phenotype, which shifted towards M2 over time. This effect was associated with soluble factors released during the initial M1 polarization phase that reactivated HIV production in U1 cells, like MDM stimulated with the TLR agonist resiquimod. Our study suggests that SARS-CoV-2-induced systemic inflammation and interaction with macrophages could influence proviral HIV-1 latency in myeloid cells in PLWH.